Impact of the Health Insurance Coverage Policy on Oral Anticoagulant Prescription among Patients with Atrial Fibrillation in Korea from 2014 to 2016 - Ko, Young-Jin; Kim, Seonji; Park, Kyounghoon; Kim, Minsuk; Yang, Bo Ram; Kim, Mi-Sook; Lee, Joongyub; Park, Byung-Joo (Journal of Korean medical science, 2018)
To evaluate oral anticoagulant (OAC) utilization in patients with atrial fibrillation after the changes in the health insurance coverage policy in July 2015. We used the Health Insurance Review and Assessment Service-National Patient Samples (HIRA-NPS) between 2014 and 2016. The HIRA-NPS, including approximately 1.4 million individuals, is a stratified random sample of 3% of the entire Korean population using 16 age groups and 2 sex groups. The HIRA-NPS comprises personal and medical information such as surgical or medical treatment provided, diagnoses, age, sex, region of medical institution, and clinician characteristics. The studied drugs included non-vitamin K antagonist OACs (NOACs) such as apixaban, dabigatran, edoxaban, and rivaroxaban, and were compared with warfarin. We analyzed drug utilization pattern under three aspects: person, time, and place. The number of patients with atrial fibrillation who were prescribed OACs was 3,114, 3,954, and 4,828; and the proportions of prescribed NOACs to total OACs were 5.1%, 36.2%, and 60.8% in 2014, 2015, and 2016, respectively. The growth rate of OACs prescription increased from 61.4 patients/quarter before June 2015 to 147.7 patients/quarter thereafter. These changes were predominantly in elderly individuals aged more than 70 years. The proportion of NOACs to OACs showed significant regional difference. The change of health insurance coverage policy substantially influenced OACs prescription pattern in whole Korean region. But the impact has been significantly different among regions and age groups, which provides the evidence for developing standard clinical practice guideline on OACs use.